Beachcomber's guide to the Northeast - Tobyne, Dan (Down East Books, 2016)
"This book describes every prominent beach, its makeup (whether sandy or rocky), and includes directions and pertinent facts about available amenities. The text includes descriptions and photos of flora and fauna, such as crabs, shells, birds, insects, fish, and whales. Also featured are the driftwood, sea glass, beach stones, and shipwrecks that can be found on these beaches"--Provided by publisher